2014
DOI: 10.1088/1468-6996/15/3/035016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of melt-spun amorphous filaments

Abstract: High-speed melt spinning of a cyclo-olefin polymer (COP) and a copolyamide (CoPA) have been performed. Differential scanning calorimetry curves of the resulting monofilaments show that they remain in an amorphous state even after hot drawing. Wide angle x-ray diffraction patterns of undrawn and drawn COP filaments show that although the material remains in an amorphous state, a degree of orientation is induced in the polymer after drawing. The amorphous filaments show an enhanced bending recovery with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Fibre ID-1143 shows higher resiliency to bending, reaching 100% within 12 s (figure 1b). From this, we can conclude that fibre ID-1143 is not plastically deformed at a bending radius of 3 mm, comparing to sole COP fibres [20]. Even with an optical cladding, the good resiliency of the COP material is preserved.…”
Section: Homogeneity and Mechanical Characterization Of The Optical Fmentioning
confidence: 69%
“…Fibre ID-1143 shows higher resiliency to bending, reaching 100% within 12 s (figure 1b). From this, we can conclude that fibre ID-1143 is not plastically deformed at a bending radius of 3 mm, comparing to sole COP fibres [20]. Even with an optical cladding, the good resiliency of the COP material is preserved.…”
Section: Homogeneity and Mechanical Characterization Of The Optical Fmentioning
confidence: 69%
“…The fiber specimens under Raman analysis were deformed to a radius of curvature of approximately 2 mm, which corresponds to applied compressive (ε c ) and tensile (ε t ) strains at the periphery of the bent fiber in the order of 6% and 1%, respectively. It is known from previous work that ε c = 6% will already induce plastic deformation in the material [5]. Micro-Raman spectroscopy performed by Herrera Ramirez et al [41] on polyamide 66 filaments under axial deformation has shown that the wavenumbers representative of the amorphous domains do not shift when the fiber is subjected to an external load for ε values of up to 12%, a value well beyond the yield point of the material.…”
Section: Analysis Of Static Bending Deformationmentioning
confidence: 96%
“…The melt-spun amorphous filaments under analysis display a significantly better recovery from a bending deformation than various semi-crystalline melt-spun fibers commercially available, such as for polyester and polyamide [5]. This is likely possible as the amorphous fibers are able to redistribute applied compressive strains in a way which prevents them from reaching their yield strain criterion at radii of curvature where semi-crystalline materials already undergo plastic deformation [5].…”
Section: Analysis Of Static Bending Deformationmentioning
confidence: 99%
See 2 more Smart Citations